2015
DOI: 10.14257/ijhit.2015.8.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Integral Criterion-Based Adaptation Control to Vibration Reduction in Sensitive Actuators

Abstract: Refer to this research, an integral criterion-based hybrid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…An alternative way to solve the chattering problem is the application of the fuzzy logic [12] in the construction of the control input. Fuzzy logic has proven to be a potent tool in the sliding mode control of time-invariant linear systems [13][14][15][16][17][18][19][20][21][22] as well as timevarying nonlinear systems [14]. It provides methods for formulating linguist rules from expert knowledge and is able to approximate any real continuous system to arbitrary accuracy.…”
Section: Figure 1 Dental Robot Manipulatormentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative way to solve the chattering problem is the application of the fuzzy logic [12] in the construction of the control input. Fuzzy logic has proven to be a potent tool in the sliding mode control of time-invariant linear systems [13][14][15][16][17][18][19][20][21][22] as well as timevarying nonlinear systems [14]. It provides methods for formulating linguist rules from expert knowledge and is able to approximate any real continuous system to arbitrary accuracy.…”
Section: Figure 1 Dental Robot Manipulatormentioning
confidence: 99%
“…Mohan and Bhanot have addressed comparative study between some adaptive fuzzy and a new hybrid fuzzy control algorithm for manipulator control. They found that self-organizing fuzzy logic controller and proposed hybrid integrator fuzzy give the best performance as well as simple structure [18][19][20][21][22].…”
Section: Figure 1 Dental Robot Manipulatormentioning
confidence: 99%
“…Uncertainty in system can causes some problems about dentistry. To solve this problem, neural network, fuzzy logic, and neurofuzzy are synergically combined with classical controller and used in nonlinear, time variant, and uncertainty plant (e.g., robot) [14][15][16][17][18][19][20].…”
Section: Figure 2 Intuitive Surgical Davinci Surgical Systemmentioning
confidence: 99%
“…The current number of researchers in this field and research societies mushrooming around the world show the attractiveness of this theory for both theoretical and practical researchers. One of the newest and most challenging technological applications is of the fuzzy logic in the control system of a dental robot, which is fundamentally unstable and with highly nonlinear dynamics [16][17][18][19][20]. In this research the main target is design PID intelligent controller to improve the robust, stability and reliability in dental robot manipulator.…”
Section: Figure 2 Intuitive Surgical Davinci Surgical Systemmentioning
confidence: 99%
See 1 more Smart Citation